2012
DOI: 10.1002/app.37875
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and mechanical behavior of LDPE/calcium carbonate nanocomposites and microcomposites

Abstract: The increase of the interest in polymer nanocomposites has been leading to continuous growing search toward nanofillers alternative to the widely known clay‐based ones. One of these possible alternatives is represented by calcium carbonate nanoparticles, which have not been widely investigated in such context. In this article, a study on the rheological and morphological behavior of different low density polyethylene‐calcium carbonate nanocomposites, compared with a reference calcium carbonate microcomposite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 49 publications
4
35
0
1
Order By: Relevance
“…However, it is known from the Literature that they are able to protect against thermal-oxidation during the processing [9,11,14,17], but they have only an indirect influence on the photo-oxidation behaviour (for instance, by interfering with the formation of double bonds), which could be seen only as far as the final conditions are concerned, while the mechanisms and paths are not altered; furthermore, all of the systems prepared and investigated here contain practically the same amount of antioxidants, therefore their presence does not influence the comparisons. The nanosized fillers were a precipitated calcium carbonate, supplied by Solvay (Belgium) under the commercial name of Socal ® 31 (in the following indicated as S31), with a calcite rhombohedral crystal structure, cube-like crystal shape and a mean particle diameter 50-100 nm [21], and a montmorillonite clay produced by Southern Clay Products (USA) and commercialized as Cloisite ® 15A (further indicated as CL15A; modified with dimethyldihydrogenated tallow-quaternary ammonium chloride quaternary surfactant; quaternary concentration = 12 meq·(100 g) -1 clay; d 001 = 3.15 nm; density = 1.66 g·cm -3 ). The coupling agent was a polypropylene grafted with maleic anhydride (PPgMA), supplied by Sigma Aldrich (USA), with maleic anhydride content 8-10 wt% and melting temperature = 156°C.…”
Section: Experimental 21 Materialsmentioning
confidence: 99%
“…However, it is known from the Literature that they are able to protect against thermal-oxidation during the processing [9,11,14,17], but they have only an indirect influence on the photo-oxidation behaviour (for instance, by interfering with the formation of double bonds), which could be seen only as far as the final conditions are concerned, while the mechanisms and paths are not altered; furthermore, all of the systems prepared and investigated here contain practically the same amount of antioxidants, therefore their presence does not influence the comparisons. The nanosized fillers were a precipitated calcium carbonate, supplied by Solvay (Belgium) under the commercial name of Socal ® 31 (in the following indicated as S31), with a calcite rhombohedral crystal structure, cube-like crystal shape and a mean particle diameter 50-100 nm [21], and a montmorillonite clay produced by Southern Clay Products (USA) and commercialized as Cloisite ® 15A (further indicated as CL15A; modified with dimethyldihydrogenated tallow-quaternary ammonium chloride quaternary surfactant; quaternary concentration = 12 meq·(100 g) -1 clay; d 001 = 3.15 nm; density = 1.66 g·cm -3 ). The coupling agent was a polypropylene grafted with maleic anhydride (PPgMA), supplied by Sigma Aldrich (USA), with maleic anhydride content 8-10 wt% and melting temperature = 156°C.…”
Section: Experimental 21 Materialsmentioning
confidence: 99%
“…According to the literature, the use of nanometric fillers for polymer/based composites allows obtaining some remarkable improvements in comparison to the neat polymer matrices. These can include enhancements of technological properties such as the elastic modulus, the tensile strength, the barrier properties and these results are even more interesting since they can be achieved upon using small filler amounts . Furthermore, polymer nanocomposites are reported to be attracting an increasing interest from the industry …”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,[8][9][10][19][20][21][22][23][24][25][26][27] Chan et al 9 reported an enhancement in mechanical properties. In their work, the good filler dispersion has resulted in significant enhancement in elastic modulus of the nanocomposites (approximately 85%), while the ultimate stress and the yield stress and strain were not strongly affected by the presence of nano-CaCO 3 particles.…”
Section: Introductionmentioning
confidence: 96%